Choriocarcinoma-like tumor in a potbellied pig (Sus scrofa). (January 2014) - Hirata, Akihiro; Miyazaki, Aya; Sakai, Hiroki; Imada, Nanae; Kitani, Ryohei; Nikami, Hideki; Yanai, Tokuma
A uterine tumor, with histological and immunohistochemical features consistent with those of human choriocarcinoma, was identified in a 10-year-old unmated female pot-bellied pig ( Sus scrofa ). The tumor showed biphasic proliferation of cytotrophoblast-like cells and syncytiotrophoblast-like cells. Immunohistochemically, the syncytiotrophoblast-like cells were positive for human chorionic gonadotropin, and both types of cells were positive for cytokeratin and negative for vimentin, octamer-binding transcription factor 4, and α-fetoprotein. Because syncytiotrophoblasts are absent in the normal porcine placenta, the tumor was diagnosed as a choriocarcinoma-like tumor.